PEOPLE’S INTERNAL DISPLACEMENT EXPERIENCES IN ETHIOPIA - YIBELTAL NEBIYU TIBEBU (Innovare Journal of Social Sciences, 2025)
Objective: This study explores the lived experiences of internally displaced persons (IDPs) in Metekel, northwestern Ethiopia, as a result of ethnic-based violence. Methods: Using a qualitative case study design, data were gathered through in-depth interviews and focus group discussions with IDPs in Chagni camp. Results: Findings reveal severe forms of trauma, including night attacks, sexual violence, property destruction, family separation, and psychosocial distress caused by state-linked ethnic violence using both traditional and modern weapons. Conclusion: The study highlights the urgent need for political, humanitarian, and development interventions to address the root causes and impacts of internal displacement in Metekel. Keywords: Internal displacement, Displacement.